Shortcomings in the Regulations of Criminal Law on Cyber Crime and Recommendations - Hoa, Nguyen Phuong (VNU Journal of Science: Legal Studies, 2024)
In the modern digital space, personal data can be attacked and used for illegal purposes. On 17 April 2023, the Vietnamese Government passed Decree No. 13/2023/ND-CP on Protecting Personal Data. The Criminal Code of Vietnam 2015 (amended in 2017) set up cyber-related crimes to protect the safety of cyber activities in general and personal data in particular. However, there are a number of shortcomings in the Criminal Code in the comparison with the Decree 13/2023/ND-CP and international treaties on cybercrime. This article analyzes these shortcomings and provides recommendations to revise relevant provisions of the Criminal Code.